No association between alcohol consumption and pancreatic cancer even among individuals genetically susceptible to the carcinogenicity of alcohol - Yan-Shen Shan (Nature Portfolio, 2021)
Abstract Inconsistent results have been reported for the association between alcohol use and pancreatic cancer, particularly at low levels of alcohol consumption. Individuals genetically susceptible to the carcinogenic effect of alcohol might have higher pancreatic cancer risk after drinking alcohol. The current study investigated the association between alcohol use and pancreatic cancer with 419 pancreatic cancer cases and 963 controls recruited by a hospital-based case–control study in Taiwan. Gene-environment interaction between alcohol use and polymorphisms of two ethanol-metabolizing genes, ADH1B and ALDH2, on pancreatic risk was evaluated. Our results showed no significant association between alcohol drinking and an increased pancreatic cancer risk, even at high levels of alcohol consumption. Even among those genetically susceptible to the carcinogenic effect of alcohol (carriers of ADH1B*2/*2(fast activity) combined with ALDH2*1/*2(slow activity) or ALDH2*2/*2(almost non-functional)), no significant association between alcohol use and pancreatic cancer was observed. Overall, our results suggested that alcohol drinking is not a significant contributor to the occurrence of pancreatic cancer in Taiwan.